Crop Yield and Nitrous Oxide Emissions following Swine Manure Application: A Meta‐Analysis. Issue 1 (1st September 2019) - Luo, Weiquan; O'Brien, Peter L.; Hatfield, Jerry L.
Abstract : Core Ideas: Swine manure is a potential nutrient source but may harm environmental quality. Crops fertilized with swine manure matched those using synthetic fertilizer. Swine manure did not increase nitrous oxide compared with synthetic fertilizer. Manure application method and conditions dictate yield and environmental impacts. Swine manure has potential for reuse as fertilizer on cropland and pastureland. Currently, producers may be hesitant to land apply swine manure because information regarding the impacts to crop production and environmental quality has been inconsistent. The objective of this research was to synthesize the literature investigating impacts of swine manure application on crop yield and soil nitrous oxide emissions as compared to synthetic fertilizer. Overall, the meta‐analysis of 39 studies shows that swine manure does not affect either crop yield or nitrous oxide emissions. However, a moderator analysis indicated that crop yield using manure fertilizer may be adversely affected in fine‐textured soils or when applied to the soil surface. While these results suggest that swine manure may be safely applied as fertilizer, producers should still be cautious with how manure is applied to capture its N value without yield losses or detrimental effects to environmental quality.